2003
DOI: 10.1177/230949900301100110
|View full text |Cite
|
Sign up to set email alerts
|

Use of Wagner Cementless Self-Locking Stems for Massive Bone Loss in Hip Arthroplasty

Abstract: Implantation of a Wagner cementless self-locking revision stem provided satisfactory results for 82% of patients. Hence, in some difficult conditions, this device is a good choice of management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…8,9 Subsequent studies reported comparable signs of femoral reconstruction, with survival rates of > 90% after five to ten years (Table II). [10][11][12][13][14][15][16][17]20,[34][35][36][37][38][39] New bone formation is promoted by numerous factors, including a low modulus of elasticity and mechanical stability, careful removal of peri-prosthetic cement and granulation tissue, and the use of a trochanteric osteotomy. 10,[14][15][16] In difficult cases, the transfemoral approach helps gain access to the femur for easier removal of the component and retained cement, creating a fracture-like situation in the proximal femur while keeping the fragments well vascularised to stimulate healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Subsequent studies reported comparable signs of femoral reconstruction, with survival rates of > 90% after five to ten years (Table II). [10][11][12][13][14][15][16][17]20,[34][35][36][37][38][39] New bone formation is promoted by numerous factors, including a low modulus of elasticity and mechanical stability, careful removal of peri-prosthetic cement and granulation tissue, and the use of a trochanteric osteotomy. 10,[14][15][16] In difficult cases, the transfemoral approach helps gain access to the femur for easier removal of the component and retained cement, creating a fracture-like situation in the proximal femur while keeping the fragments well vascularised to stimulate healing.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are the same as those in other series. 10,12,[15][16][17]20,[34][35][36][40][41][42][43][44][45] The clinical results could be open to question, because at the latest examination only 18 patients obtained an HHS > 80 points. However, these were generally elderly, and some had severe bone defects that could not have been adequately dealt with using conventional prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain scores were less in the modular tapered group, and dislocation rates were lower than that reported in the monoblock revision stems. [4][5][6][7]10,11 However despite early reports of failures, clearly there remains a role for monoblock tapered fluted stems. In fact, Bohn and Bischel recently reported a 95.2% survival rate in 129 consecutive femoral revisions using the Wagner SL revision stem.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 As it was difficult to control when the stem engaged the diaphysis and component undersizing, subsidence occurred in about 20% of patients, which altered leg lengths and/or led to instability in up to 25% of patients. [4][5][6][7] As a result many implant companies and surgeons moved to modular tapered, fluted stems.…”
Section: Advantages and Disadvantages Of Modular Tapered Stemsmentioning
confidence: 99%